COVID-19 home isolation and food consumption patterns: Investigating the correlates of poor dietary diversity in Lebanon: a cross-sectional study [version 1; peer review: 2 approved] - Maha Hoteit; Hussein Mortada; Ayoub Al-Jawaldeh; Carla Ibrahim; Rania Mansour (F1000Research, 2022)
Background: The unfurling COVID-19 pandemic has uncovered the defenselessness of the Lebanese food system leading to serious implication in maintaining a healthy sustainable lifestyle. Aim: The main purpose of this study is to examine the impact of the COVID-19 pandemic on food consumption patterns and dietary diversity of the Lebanese people. Methods: The online survey, completed between April and June 2020, consisted of a cross-sectional study on 2282 Lebanese participants (mean age: 29.36±12.221, 80.9% women) that was part of a survey across 38 different countries conducted by De Backer, C. et al. A food frequency questionnaire was used to investigate the consumption patterns along with the calculation of the Food Consumption Score (FCS), a proxy indicator of dietary diversity. Data collected on cooking attitudes, shopping, and food stock identify the community mitigation measures. Results: Home isolation due to COVID-19 induced an increase in the consumption of legumes and pulses (3.2%, p-value=0.001) and whole wheat groups (2.8%, p-value=0.03). In contrast, a decrease of 5.4%, 6.9%, 5.8%, 5.1%, 3.1%, 3.4% and 2.8% was observed in the consumption of fruits (p-value=0), vegetables (p-value=0), processed meats, poultry, and fish (p-value=0), other dairy products (p-value=0), sweet snacks (p-value=0.001), sugared beverages (p-value=0), fats and oils (p-value=0.001), respectively. The FCS decreased by 4.6%. As food-related behaviors, most cooking attitudes, and practices (10 out of 13) showed an amelioration during the lockdown and the proportions of food stocked have been changing since the start of the pandemic seeing higher amounts of pasta, rice or other grains, flour, and legumes/pulses stocked. Conclusion: To conclude, the hostile home isolation strategy followed to prevent the COVID-19 spread in Lebanon, came at a high nutritional cost, driving poor dietary diversity.